Practitioner attitudes to clozapine initiation. (5th September 2013) - Gee, S.; Vergunst, F.; Howes, O.; Taylor, D.
<x xml:space="preserve">Abstract</x> Objective Clozapine is the most effective antipsychotic for treatment‐resistant schizophrenia. It is recommended as third‐line treatment for schizophrenia in national and local guidelines. Despite this, it is underutilised. This survey aimed to clarify barriers to prescribing and elucidate factors that may improve patient access to clozapine. Method A questionnaire was made available to all staff members at South London and Maudsley NHS Foundation Trust. Results In total, 144 clinical staff completed the questionnaire. The majority (81%) of respondents were 'fairly' or 'very' familiar with clozapine prescribing guidelines. Barriers to prescribing most commonly stated as being 'very frequently' a problem were patient concerns about tolerability of clozapine or patient refusal to adhere to blood test monitoring. Staff members also felt medical complications frequently prevented clozapine prescription. Dedicated staff or day hospital placements devoted to clozapine initiation were identified as factors most likely to increase prescribing of clozapine. Conclusion Professionals identified the dominant barriers to prescribing as being patient focussed – refusal of blood test monitoring or concerns about tolerability. Clinician fears about compliance or medical complications were also important. The development of out‐patient services specifically tasked with initiating clozapine may help to increase the frequency of prescribing of clozapine earlier in treatment than is currently seen.